Few training sessions between return to play and first match appearance are associated with an increased propensity for injury: a prospective cohort study of male professional football players during 16 consecutive seasons - Bengtsson, H.; Ekstrand, J.; Waldén, M.; Hägglund, M. (British Journal of Sports Medicine, 2020)
BACKGROUND: It has been hypothesised that injury risk after return to play following an injury absence is influenced by the amount of training completed before return to competition. AIM: To analyse if the number of completed training sessions between return to play and the first subsequent match appearance was associated with the odds of injury in men's professional football. METHODS: From a cohort study, including 303 637 individual matches, 4805 first match appearances after return to play following moderate to severe injuries (=8 days absence) were analysed. Rate ratios (RRs) were used to compare injury rates in the first match appearances with the average seasonal match injury rate. Odds ratios (ORs) were used to analyse associations between the number of completed training sessions and general (all injuries), muscle, and non-muscle injury odds. RESULTS: Injury rate in the first match after return to play was increased by 87% compared with the average seasonal match injury rate (46.9 vs 25.0/1000 hours, RR=1.87; 95% CI 1.64 to 2.14). The odds of injury dropped 7% with each training session before the first match (OR 0.93; 95% CI 0.87 to 0.98). The same association was found for muscle injuries (OR 0.87; 95% CI 0.79 to 0.95) but not for non-muscle injuries (OR 0.99; 95% CI 0.91 to 1.07). CONCLUSIONS: Injury rates in the first match after injury are higher than the average seasonal match injury rate, but the propensity for player injury is decreased when players complete more training sessions before their first match.